PERMEABILITY MAP OF RESIDENTIAL SETTLEMENTS IN THE TROPICS - Antaryama, I Gusti Ngurah (DIMENSI (Journal of Architecture and Built Environment), 2002)
Source of information for ventilation design of residential settlement is generally derived from wind tunnel or, recently, CFD studies, which involves both modeling and simulation of wind flow pattern and speed. Yet this is not readily accessible to most architects. In order to gain similar objectives but without involving detailed studies, the present study introduces a graphical method of gathering information about permeability of residential. It describes how the way wind reaches and flows through built spaces and forms (streets, park/garden, buildings), and makes use of access graphs and numerical measures to indicate permeability of a given residential settlement. Since the method is still in the initial development, further study will be required for refinement and validation. Nevertheless, the method can be employed to provide information for ventilation design of low-rise residential settlements, particularly at the schematic level.